Characterization of Variants of Uncertain Significance in ACADVL Gene From a Very–Long‐Chain Acyl‐CoA Dehydrogenase Deficiency Patient - Qin Wang; Jingxin Yang; Yong Xu; Xingping Li; Nan Jiang; Jiansheng Xie (Molecular Genetics & Genomic Medicine, 2025)
ABSTRACT Background Very–long‐chain acyl‐CoA dehydrogenase deficiency (VLCADD) is a rare disorder of long‐chain mitochondrial fatty acid oxidation (FAO) caused by biallelic mutations in the acyl‐CoA dehydrogenase very–long‐chain (ACADVL) gene with autosomal recessive (AR) inheritance. Currently, the ACADVL gene has over 350 VUSs in the ClinVar database that require characterization to determine potential pathogenicity. Methods In this study, we performed functional studies and three‐dimensional protein structure analysis to identify the pathogenicity of two ACADVL VUSs in a Chinese VLCADD patient with severe clinical symptoms. Results Biallelic variants in ACADVL gene c.1055T>C (p.Met352Thr) and c.1269G>A (p.Ser423=) were identified by whole‐genome sequencing (WGS) and confirmed using Sanger sequencing. Both variants were recorded in ClinVar database with “conflicting interpretation of its pathogenicity” and need appropriate evidence for reclassification to guide family reproductive planning. Synonymous variant p.Ser423= could result in skipping of exon 12 through mini‐gene splicing experiment testing. Further functional studies reveal that both variants yield a mild‐to‐severe decrease in ACADVL mRNA and protein expression in vitro. Conclusion In this study, we determined the pathogenicity of ACADVL variants c.1055T>C (p.Met352Thr) and c.1269G>A (p.Ser423=) via experimental and in silico analysis. The findings contribute to expanding the variant spectrum in the ACADVL gene, and exploring the pathogenicity of VUS may provide us with further understanding of the disease.